1961
DOI: 10.1111/j.1365-2672.1961.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

A NOTE ON THE SYSTEMATIC POSITION OF VIBRIO FETUS

Abstract: The morphology of Vibriofetus, and of some nonpathogenic vibrios isolated from cattle, has been compared with that of 5 type cultures of Vibrio spp., including V . cholerae, and the systematic position of these bovine vibrios reviewed. Morphological differences betwwn V . fetus and the nonpathogenic bovine vibrios have been observed. These may be of assistance in their identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1962
1962
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Under routine isolation procedures, such organisms may be overlooked unless a suitable milieu is provided. Although morphologically similar to the type species of the genus Vibrio, V. cholerae (Park, 1961), the microaerophilic vibrios have been shown to differ from it in DNA base ratios and in other respects and have consequently been placed in a separate genus, Campylobacter (Sebald & V6ron, 1963). The best known of these microaerophilic vibrios is C. fetus (Vibrio fetus) (Smith & Taylor, 1919).…”
Section: Discussionmentioning
confidence: 99%
“…Under routine isolation procedures, such organisms may be overlooked unless a suitable milieu is provided. Although morphologically similar to the type species of the genus Vibrio, V. cholerae (Park, 1961), the microaerophilic vibrios have been shown to differ from it in DNA base ratios and in other respects and have consequently been placed in a separate genus, Campylobacter (Sebald & V6ron, 1963). The best known of these microaerophilic vibrios is C. fetus (Vibrio fetus) (Smith & Taylor, 1919).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have applied a large number and variety of simple tests to a small number of bacterial strains representing all but two (Vihio fetus, see Park, 1961 b, and V. metschnikovii) of the so-called vibrios available in the National Collection of Industrial Bacteria and National Collection of Type Cultures. Although the results obtained by the two authors differ in details, the classification of strains derived from these two independent studies is the same, Tables 1 and 2 show how the strains were analysed into groups; the first group in each table represents what we consider to be true members of the genus Vibrio, the second (strain 8194) exhibits characters typical of Pseztdorpumas Jlzcorescens, while the third group is comprised of strains that we regard as representatives of the genus named Lophomonas by Galarneault & Leifson (1956).…”
Section: Discussionmentioning
confidence: 99%
“…One of us (R.W.A.P.) examined a group of vibrios as part of a comparative study of the polarly flagellate bacteria commonly found in surface waters (see Park, 1961 a). The other (G.H.G.D.)…”
Section: Thirty-four Species Are Listed In the Genus Vibrio Of Bergeymentioning
confidence: 99%
“…The heterogeneity within the genus Vibrio was highlighted by Davis and Park (90,305). By examining morphological and biochemical features of most species of the genus Vibrio, they showed that it was quite artificial and concluded that at least three genera existed among the species examined.…”
Section: Numerical and Polyphasic Taxonomymentioning
confidence: 99%